Perioperative Impella 5.5 Support for Surgical Aortic Valve Replacement: Pull Back/Push Through Technique, Safeguards, and Pitfalls. Issue 2 (12th December 2022) - Al Rameni, Dina; Akay, Mehmet; Salas de Armas, Ismael; Patel, Manish K.; Patel, Jayeshkumar; Marcano, Juan; Sarateanu, Cristian Sorin; Kar, Biswajit; Gregoric, Igor D.
Abstract : In patients undergoing aortic valve surgery, preoperative reduced left ventricular ejection fraction is not uncommon and is associated with poor outcomes. Mechanical circulatory support (MCS) may be preemptively used in patients presenting with high periprocedural risk. The Impella 5.5 is a percutaneous left ventricular assist device that has been increasingly used in various cardiac surgeries. In this article, we present a step-by-step guide, safeguards, and pitfalls on how to replace the aortic valve and preserve this transaortic MCS device for postoperative support in patients with concomitant aortic valve pathology and left ventricular dysfunction.